2019
DOI: 10.3389/fimmu.2019.00829
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Extraction and B Cell Activation Enable Identification of Rare Membrane Antigen Specific Human B Cells

Abstract: Determining antigen specificity is vital for understanding B cell biology and for producing human monoclonal antibodies. We describe here a powerful method for identifying B cells that recognize membrane antigens expressed on cells. The technique depends on two characteristics of the interaction between a B cell and an antigen-expressing cell: antigen-receptor-mediated extraction of antigen from the membrane of the target cell, and B cell activation. We developed the method using influenza hemagglutinin as a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
(43 reference statements)
2
20
0
Order By: Relevance
“…B cell activation through antigen recognition is associated with upregulation of the surface marker CD69 (19). T cell education had no effect on the number of FO or MZ B cells expressing CD69 prior to CLP ( Figure 4G).…”
Section: Immune Education Increases Clp Induced Fo B Cell Responses Imentioning
confidence: 97%
“…B cell activation through antigen recognition is associated with upregulation of the surface marker CD69 (19). T cell education had no effect on the number of FO or MZ B cells expressing CD69 prior to CLP ( Figure 4G).…”
Section: Immune Education Increases Clp Induced Fo B Cell Responses Imentioning
confidence: 97%
“…Intravital microscopy has shown the relevance of Myo1f in the extravasation, migration and deformation of the nucleus of neutrophils (Salvermoser et al, 2018), and in infections with Listeria monocytogenes, the motility of Myo1f-deficient neutrophils is reduced (Kim et al, 2006). The migration of activated B cells is important for their interaction with antigens in the inflammation sites (Zimmermann et al, 2019) or to travel to germinal centers (Mesin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggested that the B cells from the severe group were activated and experienced an Ab-switching process. Moreover, expression of CD69 and FOS in B cells, which are upregulated upon activation ( 17 18 ), was higher in the severe group than in the mild group ( Fig. 1E ).…”
Section: Resultsmentioning
confidence: 95%